Competency Enhancement: Training Need Analysis among Local Authority Officer - isa, Khairunesa; yusoff, Rosman md; ahmad, Abd. Rahman; abu, Ismail; jamian, Anizam; jamin, Johanisma; palpanadan, Sarala thulasi (International Journal of Psychosocial Rehabilitation, 2020)
Competency play an important role for employee to compete in a challenging environment work place. From an organisational perspective, it becomes a competitive advantage for a company if they have a competent employee. For the labourers, it becomes an advantage to earning a higher salary and creates a good career development. The purpose of this study is to identify the level of competency (knowledge, expertise and attitude) of local authority officers and the types of training needed by the local authority officers. This explanatory research design used mixed method to collect data and involved 188 local authority officers from three different local authority. Quantitative results showed that local authority officers from three different areas have a high level of competency meanwhile output from round table discussion showed that there are several respondents who stated that local authority officers are not competent in executing work, especially in terms of knowledge.